A Fuzzy based PV-APF Controller for Mitigation of Current Harmonics - Naga Chaitanya, M; Rajesh, D; Sujith, K; Santhoshi, R; Phanendra, B (International Journal of Engineering and Technology, 2018)
This paper proposes a concept of Fuzzy based Active Power Filter for mitigating current harmonics in interconnected PV-Grid system. The PV array is connected to the utility grid by using a boost converter and a voltage source converter. For this, a three phase three wire system operated by non-linear load is considered. The increased harmonic content leads to increase in losses, decrease in power factor and many adverse effects. A Fuzzy based instantaneous PQ theory control technique is proposed in this paper for better harmonic compensation. This proposed system is tested and verified using Matlab/Simulink. The results obtained in both PI and fuzzy based APF systems are compared in the aspects of THD and active power.Â